Poor treatment outcomes and associated factors among hospitalized patients with stroke at Hiwot Fana Comprehensive Specialized Hospital, eastern Ethiopia - Zerihun Abera Ayele; Sisay Molla; Aliyi Ahmed; Teshager Worku; Addisu Seneshaw Bezabih; Biniyam Tedla Mamo (Frontiers in Stroke, 2023)
BackgroundStroke is a significant health problem in both industrialized and developing nations. It is the world's second-leading cause of death worldwide. Stroke incidence, prevalence, and death rates have grown internationally, with low- and middle-income nations suffering the greatest proportion of the burden. Stroke is a leading cause of long-term physical impairment, affecting a person's quality of life, societal engagement, independence, emotions, and productivity.ObjectiveTo determine the magnitude and factors associated with poor treatment outcomes in hospitalized adult patients with stroke.MethodsA hospital-based cross-sectional study was conducted from January 2019 to June 2021 in stroke patients admitted to the Hiwot Fana Comprehensive Specialized Hospital. This study included 290 patient charts. Data were collected by reviewing the medical charts using a well-developed data abstraction form. Data were entered into Epi-Data version 3.2 and exported to SPSS version 25.0. Descriptive statistics were used to describe study variables. Additionally, bivariable and multivariable logistic regression analyses were used to identify factors associated with poor stroke treatment outcomes. All statistical tests were set at 5% of significant threshold.ResultsAmong 290 enrolled patients, 172 (59.3%) had poor stroke treatment outcomes. The mean age of the patients was 54.7(SD: ±16.1) years, and more than half 182 (62.8%) of the participants were males. The overall average length of hospital stays for stroke patients was 8 ± 3.3 days. Age of 45–64 years (adjusted odds ratio [AOR]: 2.17, 95% CI [1.06, 4.41]), aspiration pneumonia (AOR: 2.13, 95% CI [1.06, 4.26]), systolic blood pressure ≥ 140 mm Hg/dl (AOR: 2.35, 95% CI [1.24, 4.47]), Glasgow Coma Scale score of <8 (AOR: 7.26, 95% CI [3.82, 13.8]), and serum creatinine level of ≥1 mg/dl (AOR: 2.73, 95% CI [1.46, 5.10]) were significantly associated with poor treatment outcome in adult stroke patients.ConclusionSix out of ten stroke patients had poor treatment outcomes. Age between 45 and 65 years, uncontrolled hypertension, aspiration pneumonia, low Glasgow Coma Scale score at admission, and renal injury were identified as significantly associated with poor treatment outcomes in stroke patients.